Prevalence, pattern and predictors of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) among college girls - Anitha Durairaj; Rathna Ramamurthi (Barpeta Obstetrics and Gynaecological Society, 2019)
Objective - To determine the prevalence, pattern and predictors of PMS and PMDD among college girls of South India. To identify the knowledge and attitude of college girls with PMS and PMDD. Methodology - A cross sectional questionnaire study based on Premenstrual Syndrome Screening Tool was conducted among the college student of Madurai, Tamilnadu. Results - The prevalence of moderate to severe PMS was 14.3% and PMDD was 3.7%. The commonest premenstrual symptom among college girls was fatigue/lack of energy, in the moderate to severe PMS category was anger and in the PMDD category was anxiety. Impairment of college efficiency or productivity was seen in 82.66% and 100% of students with moderate to severe PMS and PMDD respectively. The prevalence of moderate to severe PMS and PMDD correlated significantly with the mean age, education, heavy menstrual flow, dysmenorrhoea and family history of PMS and 85.6% college students with moderate to severe PMS and PMDD didn't perceived their symptoms as abnormal and only 16.4% had a physician consultation. Conclusion - PMS and PMDD are prevalent among substantial proportion of college girls with a significant negative influence on academic performance, emotional well being and behaviour. Strategies should be adopted in the college health program for timely recognition and management of PMS and PMDD in college girls.